Efficiency and determinants analysis of Chinese infrastructure PPP projects in the construction and operation stages - Xu, LiPing; Liu, Ning; Zhang, ShuXia; Qiu, HuangJing; Chen, Li; Wang, Zeyu (International Journal of Strategic Property Management, 2019)
Public-private partnerships (PPPs) are used for infrastructure projects, but they usually involve risk because of their complexity. The construction and operation stages are the core of successful infrastructure PPP projects. This study analysed the efficiency and determinants of the construction and operation stages of Chinese infrastructure PPP projects conducted by thirty provinces from 2008–2013. During the five years examined, the efficiency of infrastructure PPP projects in the construction stage exhibited a downward spiral, but showed a gradual upward trend in the operation stage. The results showed that government supervision was one of the most significant positive influences on construction efficiency, while risk allocation had a greater positive impact on efficiency during the operation stage. The evidence in this study is impactful because it provides insights for practitioners regarding key determinants for improving efficiency in the construction and operation stages of infrastructure PPP projects.